LUBAC and OTULIN regulate autophagy initiation and maturation by mediating the linear ubiquitination and the stabilization of ATG13. Issue 7 (3rd July 2021) - Chu, Yuanyuan; Kang, Yingjin; Yan, Cong; Yang, Cuiwei; Zhang, Tao; Huo, Huanhuan; Liu, Yanfen
ABSTRACT: Macroautophagy/autophagy is a membrane-mediated intracellular degradation pathway, through which bulky cytoplasmic content is digested in lysosomes. How the autophagy initiation and maturation steps are regulated is not clear. In this study, we found an E3 ubiquitin ligase complex, linear ubiquitin chain assembly complex (LUBAC) and a deubiquitinating enzyme (DUB) OTULIN localize to the phagophore area to control autophagy initiation and maturation. LUBAC key component RNF31/HOIP translocates to the LC3 puncta area when autophagy is induced. RNF31 knockdown inhibits autophagy initiation, and cells are more sensitive to bacterial infection. OTULIN knockdown, however, promotes autophagy initiation but blocks autophagy maturation. In OTULIN knockdown cells, excessive ubiquitinated ATG13 protein was recruited to the phagophore for prolonged expansion, and therefore inhibits autophagosome maturation. Together, our study provides evidence that LUBAC and OTULIN cooperatively regulate autophagy initiation and autophagosome maturation by mediating the linear ubiquitination and the stabilization of ATG13. Abbreviations: ATG: autophagy-related; CALCOCO2/NDP52: calcium binding and coiled-coil domain 2; CQ: chloroquine; CUL1-FBXL20: cullin 1-F-box and leucine rich repeat protein 20; CUL3-KLHL20: cullin 3-kelch like family member 20; CUL4-AMBRA1: cullin 4-autophagy and beclin 1 regulator 1; CYLD: CYLD lysine 63 deubiquitinase; DAPI: 4′, 6-diamidino-2-phenylindole; DUB: deubiquitinating enzyme; EBSS: Earle's Balanced Salt Solution; GFP: green fluorescent protein; GST: glutathione S-transferase; IKBKG/NEMO: inhibitor of nuclear factor kappa B kinase regulatory subunit gamma; LUBAC: linear ubiquitin chain assembly complex; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MAP1LC3B/LC3B: microtubule-associated protein 1 light chain 3B; MIM: MIT-interacting motif; mRFP: monomeric red fluorescent protein; NEDD4: NEDD4 E3 ubiquitin protein ligase; NFKB: NF-kappaB complex; OPTN: optineurin; OTULIN: OTU deubiquitinase with linear linkage specificity; PIK3C3/Vps34: phosphatidylinositol 3-kinase catalytic subunit type 3; PtdIns: phosphatidylinositol; PtdIns3K: class III phosphatidylinositol 3-kinase complex; PtdIns3P: phosphatidylinositol 3-phosphate; RBCK1/HOIL1: RANBP2-type and C3HC4-type zinc finger containing 1; RB1CC1/FIP200: RB1-inducible coiled-coil 1; RIPK1: receptor interacting serine/threonine kinase 1; RNF216: ring finger protein 216; RNF31/HOIP: ring finger protein 31; RT-PCR: reverse transcriptase polymerase chain reaction; S. Typhimurium: Salmonella enterica serovar Typhimurium; SHARPIN: SHANK associated RH domain interactor; SMURF1: SMAD specific E3 ubiquitin protein ligase 1; SQSTM1: sequestosome 1; STING: stimulator of interferon response cGAMP interactor 1; STUB1/CHIP: STIP1 homology and U-box containing protein 1; TNF/TNF-alpha: tumor necrosis factor; TNFAIP3/A20: TNF alpha induced protein 3; TRAF6: TNF receptor associated factor 6; TRIM32: tripartite motif containing 32; UBAN: ubiquitin binding in TNIP/ABIN and IKBKG/NEMO proteins; ULK1/2: unc-51 like autophagy activating kinase 1/2; USP: ubiquitin specific peptidase; UVRAG: UV radiation resistance associated; VCPIP1: valosin containing protein interacting protein 1; WIPI2: WD repeat domain, phosphoinositide interacting protein 2; ZBTB16-CUL3-RBX1: zinc finger and BTB domain containing protein 16-cullin 3-ring-box 1; ZRANB1: zinc finger RANBP2-type containing 1.